2020
DOI: 10.1111/asj.13481
|View full text |Cite
|
Sign up to set email alerts
|

Effects of grazing adaptation on intake, ruminal fermentation, blood metabolites, and body weight change in dairy cows after turning out to pasture in early spring

Abstract: Feeding management incorporating stocking for dairy cows has been widely used in temperate regions all over the world. In recent years, grazing management for dairy cows has been reevaluated due to many aspects such as animal welfare, low costs of feed, labor, manure handling, and low environmental loads. However, in temperate regions, sufficient stocking throughout the year is impossible because of the low growth of temperate grass in the winter season. Moreover, in snowy areas, cows cannot be stocked during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 26 publications
1
6
1
Order By: Relevance
“…Grazing adaptation affected changes in ruminal fermentation and blood metabolites during the first week after turning out to 1‐day grazing. However, the effects of grazing adaptation on rumen fermentation and PUN concentration observed in the present study were contrary to those observed in our previous study on non‐lactating cows (Mitani et al, 2020). The high total VFA concentration of the CON cows on day 2 of the experimental period was not necessarily promoted by ruminal fermentation, but it may be affected by the concentration effect of ruminal pool size, which was smaller due to the lower herbage intake of these cows than of the ADP cows.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Grazing adaptation affected changes in ruminal fermentation and blood metabolites during the first week after turning out to 1‐day grazing. However, the effects of grazing adaptation on rumen fermentation and PUN concentration observed in the present study were contrary to those observed in our previous study on non‐lactating cows (Mitani et al, 2020). The high total VFA concentration of the CON cows on day 2 of the experimental period was not necessarily promoted by ruminal fermentation, but it may be affected by the concentration effect of ruminal pool size, which was smaller due to the lower herbage intake of these cows than of the ADP cows.…”
Section: Discussioncontrasting
confidence: 99%
“…The results of the present study clearly indicated that the total DMI significantly decreased after turning out from indoor feeding to 1‐day grazing when the cows were not adapted to grazing. The results of continuous measurement of herbage DMI in lactating cows in the present study are similar to those reported in our previous study on non‐lactating cows (Mitani et al, 2020). The change and difference in herbage DMI during the first week of the transition period from indoor feeding to 1‐day grazing affected the performance of cows during the 4‐week period of 1‐day grazing.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations